2023
DOI: 10.1038/s41746-023-00856-1
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of the effectiveness of chatbots on lifestyle behaviours

Abstract: Chatbots (also known as conversational agents and virtual assistants) offer the potential to deliver healthcare in an efficient, appealing and personalised manner. The purpose of this systematic review and meta-analysis was to evaluate the efficacy of chatbot interventions designed to improve physical activity, diet and sleep. Electronic databases were searched for randomised and non-randomised controlled trials, and pre-post trials that evaluated chatbot interventions targeting physical activity, diet and/or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 71 publications
0
23
0
Order By: Relevance
“…This trial could not provide evidence to support whether the intervention delivered by the simplified rule-based chatbot integrated with the messaging application was better than the intervention without a chatbot. The simplified rule-based chatbot might not meet the most updated definition of a chatbot . Second, the COVID-19 pandemic and COVID-19 vaccination rollout might have affected the study outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This trial could not provide evidence to support whether the intervention delivered by the simplified rule-based chatbot integrated with the messaging application was better than the intervention without a chatbot. The simplified rule-based chatbot might not meet the most updated definition of a chatbot . Second, the COVID-19 pandemic and COVID-19 vaccination rollout might have affected the study outcome.…”
Section: Discussionmentioning
confidence: 99%
“…A chatbot is a computerized program that acts to replicate human interaction through text, speech, and visual forms of communication . The chatbot is potentially useful to deliver SOC-tailored intervention promoting SIV.…”
Section: Introductionmentioning
confidence: 99%
“…Another study comparing experiences of human coached versus a virtual chatbot coach found that the chatbot could create a coach-like experience for participants and had the advantage of being persistent and fostering greater participant autonomy by more consistently offering choices and options during the coaching chat session [78]. Moreover, a recent systematic review and meta-analysis of the effectiveness of chatbots on lifestyle behaviors found that chatbot interventions are efficacious for many of the lifestyle behaviors targeted by Vira, such as physical activity and sleep duration [79], though larger studies with more rigorous designs, objective behavioral measures, and longer follow-up are needed. There are also limited studies examining if virtual coach solutions lead to similar improvements in clinical outcomes as human-supported digital interventions.…”
Section: Effec�venessmentioning
confidence: 99%
“…Enter chatbots, which offer the potential of blending the scalability of mHealth technologies with the personalized touch of health coaching. This field, though niche, has shown considerable promise in recent years (1). With the arrival of generative AI tools such as ChatGPT in 2022, new possibilities to meet the complex and personalized requirements of health behavior modification appear vast.…”
Section: Introductionmentioning
confidence: 99%